Partially hydrolyzed, whey-based infant formula with six human milk oligosaccharides, B. infantis LMG11588, and B. lactis CNCM I-3446 is safe, well tolerated, and improves gut health: a staged analysis of a randomized trial - Picaud, Jean-Charles; Claris, Olivier; Gil-Campos, Mercedes; De La Cueva, Ignacio Salamanca; Cornette, Luc; Alliet, Philippe; Léké, André; Castanet, Mireille; Piloquet, Hugues; de Halleux, Virginie; Mitanchez, Delphine; Vandenplas, Yvan; et al. (Frontiers in Nutrition, 2025)
Background and aimsGut health and microbiome development are closely linked in early life, with human milk oligosaccharides (HMOs) playing a key role. This study reports results through 4 months of age from a trial evaluating an infant formula containing a synbiotic blend of HMOs and probiotics, focusing on growth, gastrointestinal (GI) tolerance, and gut health biomarkers from birth to 15 months.Materials and methodsHealthy infants aged ≤14 days were randomized to receive either the experimental formula (SYN; control formula supplemented with six HMOs and two probiotics [B. infantis, B. lactis]) or the control formula (CTRL; partially hydrolyzed 100% whey-based formula). A non-randomized breastfed (BF) group served as a reference. The primary endpoint was weight gain velocity in SYN vs. CTRL through 4 months of age. Secondary endpoints included fecal outcomes (abundance of bifidobacteria, immune and gut health markers), GI tolerance, and adverse events (AEs).ResultsThe full analysis set (FAS) included 313 infants (118 in SYN, 114 in CTRL, and 81 BF), while the per-protocol population (PP) included 227 infants (84 in SYN, 84 in CTRL, and 59 BF). Weight gain velocity through 4 months in the SYN group was non-inferior to that in the CTRL group in both FAS and PP analyses (both p < 0.0001). Parent-reported GI tolerance and stool patterns were similar between SYN and CTRL groups through 4 months. At 3 months, Bifidobacteria abundance was significantly higher in the SYN group compared to the CTRL group (p = 0.004). Fecal pH was lower in the SYN group than in the CTRL group (p = 0.018) and more closely resembled that of the BF group. Immune and gut health markers were similar between the SYN and BF groups. No significant differences in AEs were observed across groups.ConclusionThe synbiotic-supplemented infant formula supported healthy, age-appropriate growth, good GI tolerance, and increased the abundance of beneficial bifidobacteria through 4 months of age.Clinical trial registrationhttps://clinicaltrials.gov/study/NCT04962594.